Exploring Employee Performance Through Qualitative Methods: Insights and Implications - Syahputra, Hidayat; Eddy, Pujiono; Santoso, Pamuji Hari; Yani, Fitri; Putra, Rizaldi (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This research investigates employee performance using qualitative methods, focusing on semi-structured interviews and focus groups to uncover deeper insights into performance dynamics. By interviewing employees across various departments in a mid-sized organization and facilitating focus group discussions, the study reveals key factors influencing performance, including job satisfaction, recognition, work-life balance, and career development opportunities. Thematic analysis of the data highlights both motivators and barriers, such as inadequate resources and unclear expectations, impacting performance. The findings emphasize the value of integrating qualitative insights with quantitative metrics to develop comprehensive performance management strategies. The study concludes that addressing identified challenges and leveraging strengths can enhance employee performance and overall organizational success.